Factors Influencing Purchase Intentions of Generation Z Through TikTok Application - อาจหาญ นวมินทร์; เบ็ญกาโต ภาษิณี; มูหะหมัด พีระดา; แก้วเก็บ พรปวีณ์; เย็นมี วาทิณี; ภิรมย์คง รัญชริน; บินเซาะ สกุนตา; ศรีติสาร ฐาปานีย์; รุ่งเรืองกุล ปริตภา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
The research topic is about Factors Influencing Purchase Intentions of Generation Z Through TikTok Application aim to study 1) the level of importance of factors affecting purchase intention through the TikTok application of Generation Z, 2) the level of importance of purchase intention through the TikTok application of Generation Z, and 3) the factors affecting purchase intention through the TikTok application of Generation Z. This research used a quantitative survey method by collecting data from a sample group of TikTok users who had previous experience purchasing products through the application. A questionnaire was used as the research instrument. The sample group consisted of 400 people who had purchased products through the TikTok application. The statistical methods used included percentage, mean, standard deviation, and multiple regression analysis. The research results revealed that 1) The respondents placed the highest importance on factors affecting purchase intention through TikTok among Generation Z 2) The respondents placed the highest importance on their purchase intention and 3) The factors of trust in the application, price perception, convenience in purchasing, and engagement with content significantly influenced the purchase intention through the TikTok application of Generation Z at a statistical significance level of 0.05.